Works Rescheduling in Container Terminals - Anh Duy, Nguyen Vu (The Indonesian Institute of Science and Technology Research, 2025)
Container transportation plays a vital role in freight movement, with container yards serving as critical hubs for operations. This paper focuses on the rescheduling of handling equipment in response to unexpected crane failures, which disrupt planned tasks. To address this challenge, a heuristic algorithm is proposed, incorporating the Longest Processing Time and List Scheduling procedures. Two rescheduling strategies are evaluated through numerical experiments. The results indicate that the second strategy outperforms the first in most cases by improving efficiency, albeit with more changes to the initial schedule. The numerical examples demonstrate the effectiveness of the algorithm, achieving feasible rescheduling solutions within less than one second for all tested cases. These findings highlight the algorithm’s efficiency and practicality in real-world container yard operations.